The valuation implications of sales growth in start-up ventures - Ilanit Gavious; Dafna Schwartz (The Journal of Entrepreneurial Finance and Business Ventures, 2009)
We examine whether and how investors' reliance on financial information is affected by the rate of sales growth of a start-up venture. We find that investors discern between firms by the extent to which their products are adopted by the market. For firms that failed to increase their sales since IPO, investors perceive financial data as not providing relevant or predictive information for investment decision making. In contrast, investors seem to rely heavily on financial information provided by firms presenting a continuous increase in sales. We suggest that investors may perceive firms with a continuous increase (decrease) in sales as those that are (un)able to transfer through the technology adoption lifecycle and make the transition from an early market dominated by a few visionary customers to a mainstream market. Whereas prior studies relate changes in the value-relevance of financial statements to a firm's maturity, as measured on the basis of time (firm age), our findings indicate that the main factor affecting value-relevance is a firm's degree of market penetration.
Keywords: G1; L26; M13; M41; 650; financial statements; market penetration; start-up; sales growth; technology adoption; value-relevance; valuation implications; venture capital.